2021
DOI: 10.1177/17423953211065005
|View full text |Cite
|
Sign up to set email alerts
|

The role of social support in the experience of life with ischemic heart disease for socially disadvantaged patients: A qualitative study

Abstract: Objectives Ischemic heart disease (IHD) displays wide social inequalities that are often explained with reference to lifestyle factors. However, research indicates that social support may also play an important role in social inequality in IHD. This study aims to explore the role of social support in the experience of life with IHD for socially disadvantaged patients. Methods The study was conducted as a critical hermeneutic qualitative study in Denmark between October 2018 and August 2019. Data consist of in-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(33 citation statements)
references
References 51 publications
3
30
0
Order By: Relevance
“…While tangible support was largely emphasised in describing social network influences on health, telephone communication was an important technology that offered access to psycho-social and tangible support that was reciprocal, easily accessible and a reliable way of integrating social contact frequency. Consistent with other qualitative studies, findings from these interviews emphasised social relationships influence on health, contextual influences in everyday life and fluctuations overtime in how relationships influence health (Rasmussen et al, 2021;Sriram et al, 2018).…”
Section: Qualitative Results Discussionsupporting
confidence: 81%
“…While tangible support was largely emphasised in describing social network influences on health, telephone communication was an important technology that offered access to psycho-social and tangible support that was reciprocal, easily accessible and a reliable way of integrating social contact frequency. Consistent with other qualitative studies, findings from these interviews emphasised social relationships influence on health, contextual influences in everyday life and fluctuations overtime in how relationships influence health (Rasmussen et al, 2021;Sriram et al, 2018).…”
Section: Qualitative Results Discussionsupporting
confidence: 81%
“…Even though the participants were sampled to have a limited access to social support, the findings of the study showed that some of the participants did receive important support from a few close and caring relationships (Rasmussen, Guise, et al, 2021a). The findings showed a notable difference in how the participants lived with their illness depending on whether they had supportive social relationships or not (Rasmussen, Guise, et al, 2021a).…”
Section: Summary Of the Findings From Sub-studymentioning
confidence: 90%
“…Simonÿ et al (2018)propose a table that may be used to illustrate examples of the structural analysis. This table is included in article 1 and 3 (Rasmussen, Guise, et al, 2021a;Rasmussen, Petersen, et al, 2021) Furthermore, below Table 3 shows an example of the structural analysis across the whole dataset. In this kappa and in the articles, the structural analysis is presented in the Findings section.…”
Section: Critical Interpretation and Discussionmentioning
confidence: 99%
See 2 more Smart Citations